2023
DOI: 10.1021/acsmaterialsau.3c00025
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Poly(vinyl alcohol)-Based Conductive Semi-interpenetrating Polymer Network Fibrous Hydrogel: A Toolbox for Optimal Cross-Linking

Abstract: Cross-linking of poly(vinyl alcohol) (PVA) creates a three-dimensional network by bonding adjacent polymer chains. The cross-linked structure, upon immersion in water, turns into a hydrogel, which exhibits unique absorption properties due to the presence of hydrophilic groups within the PVA polymer chains and, simultaneously, ceases to be soluble in water. The properties of PVA can be adjusted by chemical modification or blending with other substances, such as polymers, e.g., conductive poly[3-(potassium-5-but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…For example, recently, Zakrzewska et al employed the cross-linking e-spinning of PVA/poly[3-(potassium-5-butanoate)thiophene-2,5-diyl] (P3KBT, a semiconductive polymer) to prepare a conductive fibrous hydrogel. 145 In this process, two cross-linking methods, namely, thermal treatment (160 °C, 2 h) and ethanol immersion (24 h) with heating (160 °C, 20 min), were used to fabricate semi-interpenetrating polymer networks, in which PVA was cross-linked, while non-cross-linked P3KBT was trapped in the PVA networks and remained the linear molecular form. The results indicated that thermal treatment was a more effective cross-linking method, resulting in composite materials with lower conductivity because the generated dense network structures could hinder charge transfer.…”
Section: Classification and Mechanismmentioning
confidence: 99%
“…For example, recently, Zakrzewska et al employed the cross-linking e-spinning of PVA/poly[3-(potassium-5-butanoate)thiophene-2,5-diyl] (P3KBT, a semiconductive polymer) to prepare a conductive fibrous hydrogel. 145 In this process, two cross-linking methods, namely, thermal treatment (160 °C, 2 h) and ethanol immersion (24 h) with heating (160 °C, 20 min), were used to fabricate semi-interpenetrating polymer networks, in which PVA was cross-linked, while non-cross-linked P3KBT was trapped in the PVA networks and remained the linear molecular form. The results indicated that thermal treatment was a more effective cross-linking method, resulting in composite materials with lower conductivity because the generated dense network structures could hinder charge transfer.…”
Section: Classification and Mechanismmentioning
confidence: 99%
“…To date, numerous conducting polymers and their derivatives have gained significant acceptance, including polyacetylene, polypyrrole (PPy), polyaniline (PANI), poly­( p -phenylenevinylene), poly­(3,4-ethylenedioxythiophene) (PEDOT), and polythiophene (PTh) . For example, the poly­(vinyl alcohol) nanofibers that have undergone the most effective cross-linking through the incorporation of a conducting polymer, PTh derivatives, exhibited enhanced mechanical resistance to external forces, biocompatibility, water resistance, electrical conductivity, and hydrophobicity . In short, the physicochemical tuning of CPs and multifunctional nanostructure embedded CPs are exceptionally efficient and can be tailored to a particular technique, such as in the context of biomedical or electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Poly­(vinyl alcohol) (PVA) is a water-soluble hydrophilic polymer with low toxicity, high water absorption, impressive mechanical properties, and excellent biocompatibility. , Traditional methods of cross-linking PVA involve the use of high or low temperatures (which can damage sensitive molecules) , or toxic chemicals, such as formaldehyde or glutaraldehyde (which can be irritating and potentially carcinogenic). , Herein, we employed eco-friendly cross-linking of PVA using glycerol (Gly) that can interact through hydrogen bonding, van der Waals forces, and hydrophobic interactions . Green cross-linking offers several benefits compared to traditional approaches, such as (1) eliminating the use of toxic chemicals, reducing the environmental impact and potential health hazards, and (2) operating at room temperature, minimizing the risk of damaging sensitive molecules, or compromising the material’s functionality as well as minimizing the final cost, which beneficially impacts the fabrication scalability.…”
Section: Introductionmentioning
confidence: 99%
“…16 Poly(vinyl alcohol) (PVA) is a water-soluble, hydrophilic polymer with low toxicity, high water absorption, impressive mechanical properties, and excellent biocompatibility. [17][18] Traditional methods of cross-linking PVA involve the use of high or low temperatures (which can damage sensitive molecules) 19,20 or toxic chemicals, such as formaldehyde or glutaraldehyde (which can be irritating and potentially carcinogenic). 21,22 Herein, we employed eco-friendly cross-linking of PVA using glycerol (Gly) that can interact through hydrogen bonding, van der Waals forces, and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%